Latin American Decolonial Social Studies of Scientific Knowledge: Alliances and Tensions. (November 2016) - Harding, Sandra
A distinctive form of anticolonial analysis has been emerging from Latin America (LA) in recent decades. This decolonial theory argues that important new insights about modernity, its politics, and epistemology become visible if one starts off thinking about them from the experiences of those colonized by the Spanish and Portuguese in the Americas. For the decolonial theorists, European colonialism in the Americas, on the one hand, and modernity and capitalism (and their sciences) in Europe, on the other hand, coproduced and coconstituted each other. The effects of that history persist today. Starting thought from these LA histories and current realities enables envisioning new resources for social transformations. These decolonial insights seem to receive only a passing recognition in the Latin American social studies of science and technology projects that have begun cosponsoring events and publications with northern equivalents. My focus will be primarily on the decolonial theory and on just two of its themes. One is the critical resources it offers for creating more accurate and progressive northern philosophies and histories of science as well as social studies of science. The second is insights from Latin American feminists that carry different impacts in the context of the decolonial accounts.